1996
DOI: 10.1016/s0035-9203(96)90479-4
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis caused by Cryptococcus neoformans var. gattii and var. neoformans in Papua New Guinea

Abstract: Eleven cases of cryptococcal meningitis were diagnosed and biotyped from September 1991 to August 1992 in Papua New Guinea (PNG). Seven isolates were Cryptococcus neoformans var. gattii from paediatric and adult patients, one with diabetes mellitus and 4 were C. neoformans var. neoformans from adults, of whom 2 had human immunodeficiency virus type 1 (HIV-1) infection, and one each had tuberculosis and Plasmodium vivax malaria. Significant clinical findings were headache, fever, meningism, vomiting, photophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Cryptococcosis is uncommon in children, including those with HIV/AIDS (232,282), and the same appears to be the case for C. gattii infection (213,218,232,268), with the possible exception of children in Brazil. An earlier study from PNG showed that exposure to the fungus, as demonstrated by levels of serum IgG antibody directed against C. gattii, was significantly greater in adults, and especially adult males, than in children (209), suggesting that exposure increases with age and that it occurs away from the home environment.…”
Section: Infection In Childrenmentioning
confidence: 86%
See 4 more Smart Citations
“…Cryptococcosis is uncommon in children, including those with HIV/AIDS (232,282), and the same appears to be the case for C. gattii infection (213,218,232,268), with the possible exception of children in Brazil. An earlier study from PNG showed that exposure to the fungus, as demonstrated by levels of serum IgG antibody directed against C. gattii, was significantly greater in adults, and especially adult males, than in children (209), suggesting that exposure increases with age and that it occurs away from the home environment.…”
Section: Infection In Childrenmentioning
confidence: 86%
“…Importantly, papilledema was present in 15 to 53% of patients in earlier studies (29,211,213) but in only 6% of cases in the U.S. outbreak and in 12.4% of cases in a recent Australian study (130). Optic disc swelling is typically present, with loss of definition of the disc margins.…”
Section: Clinical Findingsmentioning
confidence: 86%
See 3 more Smart Citations